物理法和化学法精制对酶解法沙丁鱼油品质的影响 "Effect of physical and chemical refining on the quality of sardine oil prepared by enzymatic hydrolysis" - 魏文聪1 ,张雪冰1 ,陶宁萍1,2 WEI Wencong1, ZHANG Xuebing1, TAO Ningping1,2 (Zhongguo youzhi)
旨在为沙丁鱼油的提取与精制工艺提供理论依据，以酶解法制备粗沙丁鱼油，采用物理法(超临界CO2萃取）与化学法对其进行精制，比较精制前后沙丁鱼油的理化指标、脂肪酸组成及挥发性成分的变化，研究不同精制方法对沙丁鱼油品质的影响。结果表明：物理法和化学法精制均可去除粗鱼油中的色素和杂质，显著降低粗鱼油的酸值和过氧化值（p<0.05），与物理法精制鱼油相比，化学法精制鱼油色泽较浅，酸值和过氧化值较低；精制后，沙丁鱼油中饱和脂肪酸相对含量降低，不饱和脂肪酸相对含量升高；沙丁鱼油中共检测出62种挥发性物质，其中醛类18种，醇类、酮类和酯类各5种，烃类25种，杂环类3种，其他类1种；物理法精制对脱除鱼油中醛类等腥味物质效果较好。综上，两种精制方法都显著提高了沙丁鱼的油品质，化学法精制鱼油的理化指标较优，但工艺烦琐，且需经进一步脱臭处理。 In order to provide theoretical basis for the extraction and refining process of sardine oil, crude sardine oil was prepared by enzymatic hydrolysis, and it was refined by physical method(supercritical CO2 extraction) and chemical method. The physicochemical characteristics, fatty acid composition and volatile components of sardine oil before and after refining were compared, and the effect of refining method on the quality of sardine oil was studied. The results showed that both the physical refining method and chemical refining method could remove the pigment and impurities, and significantly reduce the acid value and peroxide value of the crude fish oil（p<0.05). Compared with the fish oil refined by physical method, the colour of the fish oil refined by chemical method was lighter, and the acid value and peroxide value were lower. After refining, the content of saturated fatty acids in fish oil decreased, while the content of unsaturated fatty acids increased. A total of 62 volatile components were detected in fish oils, including 18 aldehydes, 5 alcohols, 5 ketones, 5 esters, 25 hydrocarbons, 3 heterocyclic compounds and 1 other compounds. The physical refining method had a good effect on removing the fishy substances such as aldehydes in fish oil. In conclusion, both refining methods can significantly improve the quality of sardine oil, the physicochemical characteristics of fish oil refined by chemical method is better, but it is complicated and requires further deodorization.